2014
DOI: 10.1038/nrn3670
|View full text |Cite
|
Sign up to set email alerts
|

Gephyrin: a master regulator of neuronal function?

Abstract: The neurotransmitters GABA and glycine mediate fast synaptic inhibition by activating ligandgated chloride channels-namely, type A GABA (GABA(A)) and glycine receptors. Both types of receptors are anchored postsynaptically by gephyrin, which self-assembles into a scaffold and interacts with the cytoskeleton. Current research indicates that postsynaptic gephyrin clusters are dynamic assemblies that are held together and regulated by multiple protein-protein interactions. Moreover, post-translational modificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
368
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 364 publications
(397 citation statements)
references
References 206 publications
15
368
1
2
Order By: Relevance
“…Also gephyrin can interact with various partners, including neuroligin 2, collibystin, or even Cdc42 to regulate cluster formation and GABA A R aggregation (7,9). These results are thus consistent with the idea that gephyrin acts as a molecular hub regulating the formation and extension of the inhibitory postsynaptic density (12). Our data now indicate that gephyrin phosphorylation on Ser305 plays a critical role in the activitydependent regulation of these clustering mechanisms.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Also gephyrin can interact with various partners, including neuroligin 2, collibystin, or even Cdc42 to regulate cluster formation and GABA A R aggregation (7,9). These results are thus consistent with the idea that gephyrin acts as a molecular hub regulating the formation and extension of the inhibitory postsynaptic density (12). Our data now indicate that gephyrin phosphorylation on Ser305 plays a critical role in the activitydependent regulation of these clustering mechanisms.…”
Section: Discussionsupporting
confidence: 79%
“…The distribution and clustering of GABA A Rs at synapses is tightly regulated through interactions with the scaffolding protein gephyrin, one of the main structural constituent of inhibitory postsynaptic densities. Gephyrin forms multimeric complexes that allow the anchoring of GABA A Rs (6) via molecular mechanisms that include phosphorylation and interactions with the guanine-nucleotide exchange factor collybistin (7)(8)(9)(10)(11)(12). In addition to changes in inhibitory strength, more recent in vivo experiments revealed that inhibitory synapses are also dynamic structures that can be formed and eliminated in response to sensory experience (13)(14)(15).…”
mentioning
confidence: 99%
“…We then examined which types of molecules construct postsynaptic membrane specializations at dopamine synapses. From their symmetric nature, we examined expression levels of the following GABAergic postsynaptic proteins: GABA A Rα1, gephyrin (a scaffolding protein interacting with GABA A and glycine receptors) and NL2 (a synaptic adhesion protein interacting with GABA A receptors and gephyrin) (20,21). All three proteins were clustered in the neuropil, and tightly apposed to VIAAT-labeled GABAergic (Fig.…”
Section: Significancementioning
confidence: 99%
“…Gephyrin is the most extensively studied scaffold responsible for organizing the inhibitory postsynaptic density, which is essential for clustering of glycine and γ-aminobutyric acid type A (GABA A ) receptors, inhibitory synaptic transmission and long-term potentiation (reviewed in refs [4][5][6]. Since the discovery of gephyrin in 1982 by Heinrich Betz's group, 7 its biochemical and cellular properties have been extensively studied.…”
Section: Introductionmentioning
confidence: 99%